Pengembangan Media Pembelajaran Menggunakan Lumio By Smart pada Mata Pelajaran TIK Siswa Kelas VII SMP Negeri 37 Samarinda - Ajeng Margareta Sari; Dewi Rosita; Eko Subastian (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2025)
This research is based on the fact that the ICT learning process still uses conventional methods and a lack of interesting learning media, resulting in students having difficulty understanding the material presented by the teacher. The aim of this research is to develop and test the feasibility of learning media using Lumio By Smart in ICT subjects for class VII students at SMP Negeri 37 Samarinda. The type of research used is development research with the ADDIE development model. Data collection techniques used observation, interview and questionnaire methods. The data analysis techniques used are qualitative analysis and quantitative analysis. The research subjects involved were 3 media experts, 1 material expert and 26 students. The results of the research showed that learning media products using Lumio By Smart were declared very suitable for use, as evidenced by the feasibility test of learning media by material experts, an average score of 4.23 was obtained in the Very Appropriate category, by media experts an average score of 12 was obtained. 82 in the Very Appropriate category, according to student assessment an average score of 116.30 was obtained in the Very Appropriate category, and the assessment from all validators obtained an average score of 39.97 in the Very Appropriate category